Re-evaluation of mastodon material from Oregon and Washington, USA, Alberta, Canada, and Hidalgo and Jalisco, Mexico - Alton C. Dooley Jr; Chris Widga; Brittney E. Stoneburg; Christopher Jass; Victor M. Bravo-Cuevas; Andrew Boehm; Eric Scott; Andrew T. McDonald; Mark Volmut (PeerJ)
The presence of at least two contemporaneous Pleistocene mastodon taxa in North America (Mammut americanum and M. pacificus) invites re-examination of specimens at the geographic margins of each species in order to determine range boundaries, overlaps, and fluctuations. Third molars from Oregon in the United States, as well as from Hidalgo and Jalisco in Mexico, were found to be morphologically consistent with M. pacificus. Washington in the United States includes a number of specimens that could not be confidently assigned to either taxon. Alberta in Canada was found to have some specimens that were consistent with M. pacificus, but others that were identified as M. americanum. The Alberta specimen referred to M. pacificus is the same tooth found to have a Pliocene divergence time from M. americanum based on mitochondrial genome data from a previous study, suggesting a deep divergence time between the two taxa. The apparent presence of both mastodon taxa in close geographic proximity has interesting paleobiogeographic implications. It is not yet clear if both taxa were present simultaneously in a given location; if not, it suggests fluctuating ranges that may reflect shifting climates and/or biomes over time. Alternatively, if both taxa were simultaneously present in the same place, it may suggest a high degree of niche partitioning in mammutids. Additional accurately dated specimens will be required to resolve this question.